Teaching school geography according to the standards-based approach: An analytical study of The American experience and its challenges - Kamil, Wafaa; Kafssi, Mohamed; Soulali, Abdelali (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to analyze the experience of teaching geography based on the standards-based approach in the American educational system, regarded as a leading model of educational reform. The study begins by examining the institutional framework and the reference educational documents that guide this approach, focusing on the geography curriculum at key assessment levels (4th, 8th, and 12th grades). The research employs a descriptive-analytical methodology using content analysis to review six official educational reference documents, including the National Geography Standards and the National Assessment of Educational Progress (NAEP) Framework. The study seeks to answer the following central question: To what extent has the American educational system, based on the standards-based approach, achieved tangible improvements in the outcomes geography teaching? The findings reveal that the standards-based approach has contributed to clarifying educational objectives and enhancing learners' spatial thinking and critical analysis skills. It has also reinforced essential geographical skills, such as formulating geographical questions, gathering information from diverse sources, organizing data, and analyzing it to interpret geographical phenomena. This focus on skills has established a solid knowledge base that enables learners to analyze geographical phenomena and apply acquired concepts in real-life situations. However, challenges persist in implementing this approach, particularly due to decentralization across states and disparities in educational resources, leading to gaps in educational quality. The study recommends leveraging the American experience to enhance teaching geography within the Moroccan context.
Keywords: American education system; School geography; standards-based approach; geographical skills; content standards; performance standards